Controllability and Observability Lectures given at a Summer School of the Centro Internazionale Matematico Estivo (C.I.M.E.) held in Pontecchio (Bologna), Italy, July 1-9, 1968 - Evangelisti, E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
R.E. Kalman: Lectures on controllability and observability.- E. Kulikowski: Controllability and optimum contro.- A. Straszak: Supervisory controllabilityl.- L. Weiss: Lectures on controllability and observability.
R.E. Kalman: Lectures on controllability and observability -- E. Kulikowski: Controllability and optimum contro -- A. Straszak: Supervisory controllabilityl -- L. Weiss: Lectures on controllability and observability.
Keywords: System theory; Calculus of variations; Systems Theory, Control; Calculus of Variations and Optimal Control; Optimization